2020
DOI: 10.1093/ibd/izaa181
|View full text |Cite
|
Sign up to set email alerts
|

The Thrilling Journey of SARS-CoV-2 into the Intestine: From Pathogenesis to Future Clinical Implications

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has a direct impact on the gastrointestinal system, as up to 50% of fecal samples from coronavirus disease 2019 (COVID-19) patients contain detectable viral RNA despite a negative rhino-pharyngeal swab. This finding, together with an intestinal expression of angiotensin conversion enzyme 2 protein, suggests a possible fecal-oral transmission for SARS-CoV-2. Furthermore, gastrointestinal (GI) symptoms are common in COVID-19 patients includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 101 publications
(120 reference statements)
1
39
0
4
Order By: Relevance
“…Gastrointestinal symptoms can occur in a broad range of SARS-CoV-2 patients and can sometimes precede the respiratory involvement and be the first manifestation of the infection [ 46 ]. Indeed, gut epithelium expresses the ACE2 receptor, recognized by SARS-CoV-2 to enter host cells, where the virus starts to replicate and to elicit immune system activation characterized by pro-inflammatory cytokines and immune cell recruitment [ 47 ]. Possibly, the immune response could lead to a dysbiosis with a propagation of the pro-inflammatory state [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal symptoms can occur in a broad range of SARS-CoV-2 patients and can sometimes precede the respiratory involvement and be the first manifestation of the infection [ 46 ]. Indeed, gut epithelium expresses the ACE2 receptor, recognized by SARS-CoV-2 to enter host cells, where the virus starts to replicate and to elicit immune system activation characterized by pro-inflammatory cytokines and immune cell recruitment [ 47 ]. Possibly, the immune response could lead to a dysbiosis with a propagation of the pro-inflammatory state [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gut epithelium expresses the ACE2 receptor, recognized by SARS-CoV-2 to enter host cells, where the virus starts to replicate and to elicit immune system activation characterized by pro-inflammatory cytokines and immune cell recruitment [ 47 ]. Possibly, the immune response could lead to a dysbiosis with a propagation of the pro-inflammatory state [ 47 ]. Following oral administration, abundant LF remains on the lining of the gastrointestinal tract [ 48 ], and thus it may be plausible that LF could protect host cells against infection by SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…16 Several other reports described the detection of SARS-CoV-2 RNA in stool samples. 22,24 A comprehensive metaanalysis 25 included 95 studies and 2149 patients. The authors 25 found that 934 patients (43%) had one or more SARS-CoV-2positive sampling sites (stool or anal swab).…”
Section: Key Pointsmentioning
confidence: 99%
“…ACE-2 is abundantly expressed in the epithelium of the respiratory tract as well as the oral cavity, intestine and colon ( Lamers et al, 2020 ; Qian et al, 2020 ). It is evident now that a considerable proportion of COVID-19 patients demonstrate gastrointestinal symptoms including nausea, vomiting, diarrhea, and abdominal pain ( Cheung et al, 2020 ; Zhou et al, 2020 ; Scaldaferri et al, 2020 ). SARS-CoV-2 RNA has been detected in more than 50% of patients’ stool specimens ( Wolfel et al, 2020 ; Wang et al, 2020 ; Huang et al, 2020 ; Cha et al, 2020 ), and several studies have confirmed that the virus detected in stool is infectious ( Xiao et al, 2020 ; Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%